Answers

2015-06-28T16:52:22+05:30
We can write it as
sin60sin10sin50sin70= \sqrt{3}  /16
= \sqrt{3} /2(sin10sin50sin70)
= \sqrt{3} /2*1/2(2sin10sin50sin70)
= \sqrt{3} /4(2sin10sin50.sin70)
since
{2sinAsinB=cos(A-B)-cos(A+B)}
= \sqrt{3} /4(cos(50-10)-cos(50+10)*)sin70
= \sqrt{3} /4(coc40-cos60)sin70
= \sqrt{3} /4(sin70cos40-sn70cos60)
= \sqrt{3} /8(2sin70cos40-sin70)
since
{2sinAcosB=sin(A+B)+sin(A-B)}
= \sqrt{3} /8(sin(70+40)+sin(70-40)-son70)
= \sqrt{3} /8(sin110+sin30-sin70)
= \sqrt{3} /8(sin70+1/2-sin70)
= \sqrt{3} /16







0